Manajemen Kepala Madrasah dalam Pengembangan Karir Guru di Madrasah Aliyah Negeri 5 Batanghari - Linziyatul Maula; Jamilah Jamilah; Minnah Elwiddah (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The purpose of this research is to analyze the Management of Madrasah Principals in Teacher Career Development, this research was conducted at MAN 5 Batanghari. the variables used in this study were management, the role of the madrasah/school principal, and teacher career development. This research is descriptive and qualitative. data collection is used through observation, interviews, and documentation. The role of the Head of the Madrasa/school includes Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator. There are two types of teacher development, namely Career Development and Professional Development. So it can be concluded: 1) Management of Madrasah Heads in Teacher Career Development at Madrasah Aliyah Negeri 5 Batanghari; 2) Inhibiting Factors of Madrasah Principal Management in Teacher Career Development at Madrasah Aliyah Negri 5 Batanghari; and 3) Efforts Made by the Head of Madrasah in Developing Teacher Careers at Madrasah Aliyah Negeri 5 Batanghari.